On Georg Simmel's Einleitung in die Moralwissenschaft: Preliminary Methods, Problems, and Concepts for a Critique of Modern Monetary Economics - Lewkow, Lionel (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2020)
The aim of this article is to expose some threads of continuity between Philosophie des Geldes and a less explored writing of Georg Simmel’s theoretical trajectory, namely: Einleitung in die Moralwissenschaft. To this end, I argue that in this early text Simmel proposes a psychological, sociological, and historical method to examine morality issues, which he later replicates in his approach regarding modern monetary economics. At the same time, I state that both works share resemblances in terms of the exposed topics: The opus magnum of 1900, like that early writing, gives great relevance to ethical issues. On this basis, I evidence the methodological affinity between these texts by comparing the Berliner’s treatment of moral duty, on the one hand, and economic value, on the other. Having done this, I explain how the thesis on the conflict of values delineated by young Simmel is then revisited in Philosophie des Geldes to account for the tension between economic value and the value of people.